Pengembangan Media Buku Saku Berbasis Problem Based Learning Pada Mata Pelajaran IPS Kelas 3 di Sekolah Dasar - Agist Hasanah; Yustia Suntari; Petrus Paulus Mbette Suhendro (DPPM Universitas Pelita Bangsa, 2026)
This research aimed to develop a Problem Based Learning (PBL)-based pocket book entitled “Pocket Explorer: Tradisi Nusantara” for Grade III elementary Social Studies learning. The study applied the Research and Development (R&D) method using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 29 students, including 3 students in one-to-one evaluation, 6 students in small group evaluation, and 20 students in field testing. Data collection techniques included interviews, observations, questionnaires, documentation, and expert validation sheets. The findings showed that the developed media was categorized as highly feasible. One-to-one evaluation obtained 95%, small group evaluation reached 99%, and field testing achieved 94%. Teacher responses obtained 100%, indicating that the product was highly practical and effective for classroom learning. The developed pocket book successfully improved students’ learning motivation, critical thinking skills, participation, and understanding of cultural diversity materials. Therefore, the product is appropriate to be implemented as innovative learning media in elementary schools.